The Economic Costs of Unsupplied Electricity in Nigeria’s Industrial Sector: The Roles of Captive Power Generation and Firm Characteristics - Agwu, George Abuchi; Uwazie, Iyke Uwazie; Agbanike, F. Tobechi; Enyoghasim, Oguwuike Michael; Anochiwa, Lasbrey; Ogbonnaya, Ikwor Okoroafor; Durueke, Chima Nwabugo (International Journal of Energy Economics and Policy, 2019)
Power failure is the most influential business constraint in Nigeria. In this study we pursue answers to two questions concerning policies to mitigate the problem. In the first, we model firms’ perception of power failure constraint and found that small and medium enterprises are most constrained. In the second, we examined firms’ willingness to pay to avoid power outages and found that on average and ceteris paribus, firms are willing to commit extra 15% of their annual sales to ensure uninterrupted power supply. Furthermore, captive power generating firms are even willing to pay more for uninterrupted power supply. The analysis was based on a sample of 2,676 firms compiled from 2014 World Bank’s Enterprise Survey (WBES) for Nigeria. The empirical estimations were based on ordered probit and censored Tobit models respectively. Keywords: Power outages; industrial sector; captive power generation; firm JEL Classifications: L6; D21; C5 DOI: https://doi.org/10.32479/ijeep.7681